U stóp kameleona. Oblicza XIX-wiecznego Paryża w epistolografii Elizy z Branickich Krasińskiej - Klaudia Jeznach (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria)
This article is an attempt to look at the Parisian correspondence of Eliza Branicka Krasińska, wife of the great poet Zygmunt Krasiński, as a story about the 19th century capital of France. The everyday life, political and social events described in Elżbieta Krasińska's letters show Paris as a city with two faces. Following the aristocrat, we reach the art studios of the most outstanding painters, watch performances in theaters and operas, and also taste the latest French literature. The prose of life is shown against the background of great history and internal changes taking place in France.